Diagnosis of Malaria Gametocytes Using MP ICT Vs PCR in Infected Patients: A Cross-Sectional Study of Asymptomatic Relatives - Hina Hakim, Asma Faraid, Syed Motahir Ali Shah, Fatima, Sara Mariyum, Shumaila Asim, (Pakistan Journal of Medical & Health Sciences, 2022)
In high-risk situations, asymptomatic malarial gametocyte carriers promote malaria transmission. It may spread illness if it is constantly available as a vast undetected reservoir of Malaria. Subjects with malarial gametocytes in their circulation but no symptoms may be a hidden reservoir of the illness. Objectives: To determine the prevalence rate of subjects without symptoms who have gametocytes in their blood and live in the same housing as a malaria patient. Methodology: This study was carried out at Mercy Teaching Hospital Peshawar and Khyber Teaching Hospital Peshawar. The study duration was 10 months from October 2 to December 28, 2020. Once malaria cases were identified, patients were asked about nearby family members who did not have symptoms or tested negative for malarial infection using ICT. All the data was collected and then analyzed by SPSS version 23. Results: A total of 100 participants were included in the current study. Our results revealed that all participants showed a negative result for MP ICT. In contrast, Malarial gametocyte in blood PCR was detected among 18(18%) and not detected in 82(82%) of the study participants) Conclusion: According to the study results, many asymptomatic close relatives of patients living in the same house have malarial gametocytes. The most often afflicted direct family members were the mother and father, followed by sisters. PCR is the only tool for identifying malarial gametocytes, while ICT is ineffective at detecting carriers. Keywords: Diagnosis, Malaria Gametocytes,Mp,Pcr,A Cross-Sectional Study